GMP-compliant production of [68Ga]Ga-NeoB for positron emission tomography imaging of patients with gastrointestinal stromal tumor - Marc Pretze; Laura Reffert; Steffen Diehl; Stefan O. Schönberg; Carmen Wängler; Peter Hohenberger; Björn Wängler (SpringerOpen, 2021)
Abstract Background [68Ga]Ga-NeoB is a novel DOTA-coupled Gastrin Releasing Peptide Receptor (GRPR) antagonist with high affinity for GRPR and good in vivo stability. This study aimed at (1) the translation of preclinical results to the clinics and establish the preparation of [68Ga]Ga-NeoB using a GMP conform kit approach and a licensed 68Ge/68Ga generator and (2) to explore the application of [68Ga]Ga-NeoB in patients with gastrointestinal stromal tumors (GIST) before and/or after interventional treatment (selective internal radiotherapy, irreversible electroporation, microwave ablation). Results Validation of the production and quality control of [68Ga]Ga-NeoB for patient use had to be performed before starting the GMP production. Six independent batches of [68Ga]Ga-NeoB were produced, all met the quality and sterility criteria and yielded 712 ± 73 MBq of the radiotracer in a radiochemical purity of > 95% and a molar activity of 14.2 ± 1.5 GBq/μmol within 20 min synthesis time and additional 20 min quality control. Three patients (2 females, 1 male, 51-77 yrs. of age) with progressive gastrointestinal stromal tumor metastases in the liver or peritoneum not responsive to standard tyrosine kinase inhibitor therapy underwent both [68Ga]Ga-NeoB scans prior and after interventional therapy. Radiosynthesis of 68Ga-NeoB was performed using a kit approach under GMP conditions. No specific patient preparation such as fasting or hydration was required for [68Ga]Ga-NeoB PET/CT imaging. Contrast-enhanced PET/CT studies were performed. A delayed, second abdominal image after the administration of the of [68Ga]Ga-NeoB was acquired at 120 min post injection. Conclusions A fully GMP compliant kit preparation of [68Ga]Ga-NeoB enabling the routine production of the tracer under GMP conditions was established for clinical routine PET/CT imaging of patients with metastatic GIST and proved to adequately visualize tumor deposits in the abdomen expressing GRPR. Patients could benefit from additional information derived from [68Ga]Ga-NeoB diagnosis to assess the presence of GRPR in the tumor tissue and monitor antitumor treatment.